SISTEM INFORMASI ANGGARAN PADA PT. ARDHI KARYA TEKNIK - Rusmawan, Uus (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
PT. Ardhi Karya Teknik is a company engagedin construction, painting, cooling engineeringand information technology. This companyexperiences difficulties in managing finances,especially in terms of budget provision anduse, the concentration of problems revolvesaround the budget allocation for operationalcosts that are routinely issued every year andthe facts in the field regarding the use of thebudget. Therefore it is necessary to have abudget application that is able to manage andprovide accurate information about thecompany budget. The method used in thisresearch is waterfall. After the application ismade and implemented in the company, thebudget allocation process and reports on itsuse can be presented quickly and accuratelyand can help the parties involved in thecompany to make the necessary decisions.